2020
DOI: 10.3389/fphys.2020.604983
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Elastic Band Based Plyometric Exercise on Explosive Muscular Performance and Change of Direction Abilities of Male Team Handball Players

Abstract: This study examined the effects of incorporating 8 weeks of bi-weekly lower limb elastic band based loaded plyometric training into the in-season regimen of junior handball players. Participants were assigned between control (n = 15, age: 18.1 ± 0.5 years, body mass: 73.7 ± 13.9 kg, height: 1.82 ± 0.06 m, body fat: 14.4 ± 6.0%) and experimental groups (n = 14, age: 17.7 ± 0.3 years, body mass: 76.8 ± 10.7 kg, height: 1.83 ± 0.04 m, body fat: 13.4 ± 3.8%). Measures obtained before and after the intervention inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 32 publications
(70 reference statements)
2
22
0
Order By: Relevance
“…There are few studies evaluating jump performance after a combined PSSCoD training program. Our data are in accordance with the existing literature, which has reported improved jump performance after several programs, including combined PSSCoD training, plyometric training with and without external load, change-of-direction training, and resistance training [1,9,19,20,[22][23][24][25]31,33].…”
Section: Effect Of Training On Jump Performancesupporting
confidence: 91%
See 2 more Smart Citations
“…There are few studies evaluating jump performance after a combined PSSCoD training program. Our data are in accordance with the existing literature, which has reported improved jump performance after several programs, including combined PSSCoD training, plyometric training with and without external load, change-of-direction training, and resistance training [1,9,19,20,[22][23][24][25]31,33].…”
Section: Effect Of Training On Jump Performancesupporting
confidence: 91%
“…Subsequently, participants performed a vertical jump by driving themselves up, keeping straight legs throughout the flight time. The CMJ was similar but began from upright, followed by a downward movement to a knee angle of 90 • then a maximal upwards jump [23]. One minute of rest was allowed between the three trials of each test.…”
Section: Squat and Countermovement Jumpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are in accordance with existing literature, which has reported improved sprint performance after several programs, including LPaSS training [24], loaded plyometric training [17,18,28], and loaded sprint training [20,21,47]. Recently, Hammami et al [24] examined the effects of 10-week LPaSS training in male U17 soccer players and noted improved sprint performance over 5, 10, 20, 30, and 40 m. Moreover, Kargarfard et al [28] observed improved 30 m sprint times following unloaded plyometric and short sprints training in U19 male soccer players. Indeed, gains in sprint performance as a result of unloaded plyometric and short sprints training in male U15 soccer players have previously been observed [27].…”
Section: Effect Of Training On Sprint Performancesupporting
confidence: 93%
“…All participants also participated in weekly 60 min school physical education sessions. The planning of training time (technical-tactical and physical) is frequently used in research that has studied the effects of one type of training program on the athletic performance of participants [27,28]. Strength and conditioning training was performed twice a week.…”
Section: Experimental Designmentioning
confidence: 99%